The Contribution of Indigenous State Apparatus in Building the Community of Ureng Country - Laitupa, Patma Sari; Abas, Aisa; Tuharea, Jumiati (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Village development is an activity that covers all aspects of life in village society. Negeri Adat is a customary law community unit that is territorial genealogical in nature which has territorial boundaries, which has the authority to regulate and manage the interests of the local community based on the rights of origin and local customs which are recognized and respected within the system of government of the unitary State of the Republic of Indonesia. Every development activity carried out by government staff must be notified to the Saniri and also in the implementation of the development there must be a discussion or exchange of opinions by the government staff with the traditional land apparatus, namely the Saniri. The writing of this thesis discusses "The Contribution of Indigenous Country Apparatuses in Building the State of Ureng Society." The problems discussed in this study are: 1. The role of the Indigenous State apparatus in building the people of Negeri Ureng. 2. Efforts of Indigenous Country apparatus in building the Ureng Country Community. 3. Supporting and inhibiting factors for the Indigenous Country apparatus in developing the Negeri Ureng community. The type of research used in this research is descriptive qualitative with observation and interview techniques and using qualitative analysis techniques. The results of this study indicate that the role of the customary land apparatus in building society is very important and very necessary for the progress of the development of the Ureng Negeri community. Because the customary land apparatus plays a role in development as a supervisory institution. The efforts of the customary land apparatus in developing the Ureng country community are by always providing guidance to the existing younger generation. The supporting factors for each job need support from traditional leaders. The inhibiting factors for traditional instruments in building the Ureng country community are the time factor, the weather factor, the ADD factor, the location factor.